Biogas carbon dioxide reforming catalyst, its manufacturing method, and hydrogen production device using the same

By using nickel-based catalysts in biogas, the problems of catalyst deactivation and reaction tube blockage in carbon dioxide modification reaction in biogas are solved, and efficient hydrogen energy production and energy efficiency improvement are achieved.

JP7669031B2Active Publication Date: 2025-04-28NAT INST FOR MATERIALS SCI
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021080550
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-11
Publication Date
2025-04-28
Estimated Expiration
2041-05-11

Smart Images

  • Figure 0007669031000005
    Figure 0007669031000005
  • Figure 0007669031000006
    Figure 0007669031000006
  • Figure 0007669031000007
    Figure 0007669031000007
Patent Text Reader

Abstract

To provide a biogas CO2 reforming catalyst for producing hydrogen without removing CO2 in biogas, a method for producing the same and a hydrogen production device using the same.SOLUTION: A biogas carbon dioxide (CO2) reforming catalyst includes a honeycomb structure composed of a metal foil, and a metal active layer composed of metal particles supported on the honeycomb structure, the metal particles at least including nickel (Ni). The metal particles may include a further metal element, Re and / or Ce.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for reforming biogas into carbon dioxide (CO2), a method for producing the same, and a hydrogen production device using the same. [Background technology]

[0002] In order to achieve the goal of a decarbonized, carbon-neutral society, which would mean reducing greenhouse gas emissions to zero overall, it is essential to move away from our current reliance on fossil fuels and build a sustainable energy supply system based on all renewable energy resources, including biomass.

[0003] In recent years, many projects have been carried out to utilize wet biomass using methane fermentation technology, but most use of the produced biogas (containing mainly methane and carbon dioxide; typical composition: 60% methane, 40% carbon dioxide) is limited to direct combustion or power generation, which are low thermal efficiency methods that result in CO2 emissions.

[0004] Recently, research and development of technology to convert biogas into hydrogen energy has begun, but the content of such technology is limited to the separation and removal of CO2 from biogas, and only the use of methane (see, for example, Patent Document 1). Therefore, if technology could be established to convert biogas into hydrogen energy by effectively utilizing CO2, it would be possible to significantly reduce the cost of converting biogas into hydrogen and achieve the greatest CO2 reduction effect.

[0005] Meanwhile, there are technologies for producing synthetic gas from methane using various catalysts (see, for example, Patent Document 2 and Non-Patent Document 1). Patent Document 2 reports steam reforming of methane (CH4+H2O=3H2+CO) using a catalyst equipped with a metal active layer of nickel, nickel-rhenium alloy, or nickel-ruthenium alloy on a nickel foil honeycomb structure. However, there are no reports of using the catalyst of Patent Document 2 for reforming biogas.

[0006] Non-Patent Document 1 reports on the CO2 reforming of methane (dry reforming, CH4+CO2=2H2+2CO) using a nickel-based honeycomb catalyst that has a stainless steel honeycomb structure with a porous alumina layer and nickel particles in the pores.

[0007] The CO2 reforming of methane has a similar reaction formula to that of CO2 reforming using CO2 in biogas, but in CO2 reforming of methane, catalyst deterioration due to carbon deposition and the resulting blockage of the reaction tube have been problems. In addition, the methane in CO2 reforming of methane usually comes from natural gas, and the CO2 comes from thermal power generation, so the source of the reactant gas is different from that in CO2 reforming of biogas. Furthermore, the stoichiometric ratio of methane / CO2 in the CO2 reforming reaction formula of methane is 1, but in CO2 reforming of biogas, even though the reaction formula is similar, the stoichiometric ratio of methane / CO2 in biogas is approximately 1.5. Even though the reactions are similar, the catalysts used in CO2 reforming of methane cannot necessarily be applied to CO2 reforming of biogas. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-206402 A [Patent Document 2] JP 2002-028490 A [Non-patent literature]

[0009] [Non-Patent Document 1] Choji Fukuhara et al.,Applied Catalysis A: General,468,2013,18-25 Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a biogas CO2 reforming catalyst for producing hydrogen without removing CO2 from biogas, a production method thereof, and a hydrogen production device using the same. [Means for solving the problem]

[0011] The biogas carbon dioxide (CO2) reforming catalyst of the present invention comprises a honeycomb structure made of metal foil and a metal active layer made of metal particles supported on the honeycomb structure, the metal particles containing at least nickel (Ni), thereby solving the above-mentioned problems. The metal particles may comprise at least one further metal element selected from the group consisting of rhenium (Re), cerium (Ce), manganese (Mn), molybdenum (Mo), tungsten (W), chromium (Cr), tantalum (Ta), hafnium (Hf), osmium (Os), tin (Sn), zinc (Zn), lanthanum (La), magnesium (Mg), calcium (Ca), scandium (Sc), yttrium (Y), iron (Fe), cobalt (Co), aluminum (Al), silicon (Si), and copper (Cu). The further metallic element may be Re and / or Ce. The metal particles may be composed of Ni and Re or Ce, the Ni being in the range of 10 wt % or more and 80 wt % or less, and the Re or Ce being in the range of 20 wt % or more and 90 wt % or less. The Ni content may be in the range of 45 wt % or more and 60 wt % or less, and the Re or Ce content may be in the range of 40 wt % or more and 55 wt % or less. The metal particles may contain Ni, Re and Ce, the Ni being in the range of 10 wt% or more and 75 wt% or less, the Re being in the range of 5 wt% or more and 40 wt% or less, and the Ce being in the range of 0.5 wt% or more and 50 wt% or less. The Ni may be in the range of 25 wt % or more and 35 wt % or less, the Re may be in the range of 25 wt % or more and 35 wt % or less, and the Ce may be in the range of 25 wt % or more and 35 wt % or less. The metal particles may have a particle size in the range of 1 nm to 500 nm. The metal particles may have a particle size in the range of 10 nm to 200 nm. The metal foil may be nickel or a nickel-based alloy, an iron-based alloy, or stainless steel. The honeycomb structure has 400 cells / in 2 More than 2500 cells / in 2 It may have the following cell densities: The method for producing a biogas carbon dioxide (CO2) reforming catalyst of the present invention includes the steps of impregnating a honeycomb structure made of metal foil with a solution of a strong nickel (Ni) acid salt to form a powder layer of a strong Ni acid salt on the pore surfaces of the honeycomb structure, thermally decomposing the powder layer of the strong acid salt to form an oxide particle layer of Ni, and reducing the oxide particle layer to form a metal active layer made of metal particles containing Ni, thereby solving the above-mentioned problem. Following the formation of the Ni ferroic acid salt powder layer, a further ferroic acid salt of a metal element is added. Acid salts forming a powder layer, wherein the further metal element may be at least one selected from the group consisting of rhenium (Re), cerium (Ce), manganese (Mn), molybdenum (Mo), tungsten (W), chromium (Cr), tantalum (Ta), hafnium (Hf), osmium (Os), tin (Sn), zinc (Zn), lanthanum (La), magnesium (Mg), calcium (Ca), scandium (Sc), yttrium (Y), iron (Fe), cobalt (Co), aluminum (Al), silicon (Si) and copper (Cu). Following the formation of the Ni oxide particle layer, a further metal element is added to the oxide particle layer. Acid saltsforming a powder layer and thermally decomposing the powder layer of a strong acid salt of the further metal element to form an oxide particle layer of the further metal element, wherein the further metal element may be at least one selected from the group consisting of rhenium (Re), cerium (Ce), manganese (Mn), molybdenum (Mo), tungsten (W), chromium (Cr), tantalum (Ta), hafnium (Hf), osmium (Os), tin (Sn), zinc (Zn), lanthanum (La), calcium (Ca), scandium (Sc), yttrium (Y), iron (Fe), cobalt (Co), magnesium (Mg), aluminum (Al), silicon (Si) and copper (Cu). The strength of the Ni Acid salts Prior to forming the powder layer, the pore surfaces of the honeycomb structure may be subjected to an acid treatment. The acid treatment may use a strong acid selected from the group consisting of nitric acid, hydrochloric acid and sulfuric acid. The hydrogen production device of the present invention comprises a supply unit that supplies biogas, and a catalytic reaction unit that causes a carbon dioxide (CO2) reforming reaction from the biogas supplied from the supply unit, and the catalytic reaction unit is equipped with a carbon dioxide (CO2) reforming catalyst for the biogas, thereby solving the above-mentioned problems. The supply unit may further supply water vapor in addition to the biogas. Effect of the Invention

[0012] The carbon dioxide (CO2) reforming catalyst of biogas of the present invention comprises a honeycomb structure made of metal foil and a metal active layer made of metal particles supported on the honeycomb structure, the metal particles containing at least nickel (Ni). This enables CO2 reforming of biogas and production of synthesis gas containing hydrogen. In particular, since the catalyst has excellent resistance to carbon deposition, there is no risk of clogging of the reaction tube and it can be used for a long time. In addition, since biogas can be reformed at a relatively low temperature of about 500 to 800°C, if the catalyst of the present invention is adopted, a hydrogen production device using biogas with improved energy efficiency can be provided. In addition, the catalyst of the present invention can also be applied to CO2 reforming of methane from natural gas and petroleum. [Brief description of the drawings]

[0013] [Figure 1] Schematic diagram showing the biogas CO2 reforming catalyst of the present invention. [Diagram 2] A flow chart showing the manufacturing process of the CO2 reforming catalyst of the present invention. [Diagram 3] Another flowchart showing the manufacturing process of the CO2 reforming catalyst of the present invention [Figure 4] Yet another flowchart showing the manufacturing process of the CO2 reforming catalyst of the present invention. [Diagram 5] Schematic diagram showing a hydrogen production device of the present invention. [Figure 6] FIG. 1 shows SEM images of samples of Examples 3 and 4. [Figure 7] FIG. 1 shows methane conversion (A) and CO2 conversion (B) by CO2 reforming of biogas using samples from Examples 1 to 4. [Figure 8] Graph showing the change in internal pressure in the reaction tube during CO2 reforming of biogas using the sample of Example 4. [Figure 9] FIG. 1 shows an SEM image of the sample of Example 4 after reaction. [Figure 10] FIG. 1 shows the TGA curve of the sample of Example 4 after reaction. [Figure 11] FIG. 1 shows methane conversion (A) and CO2 conversion (B) by CO2+H2O co-reforming of biogas using samples from Examples 1 to 4. [Figure 12] A diagram showing the change in internal pressure in the reaction tube during CO2+H2O co-reforming of biogas using the sample of Example 4. [Figure 13] FIG. 1 shows an SEM image of the sample of Example 4 after reaction. [Figure 14] FIG. 1 shows the TGA curve of the sample of Example 4 after reaction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that like elements are given like reference numerals and their description will be omitted.

[0015] (Embodiment 1) In the first embodiment, a biogas CO2 reforming catalyst and a production method thereof according to the present invention will be described.

[0016] FIG. 1 is a schematic diagram showing a biogas CO2 reforming catalyst of the present invention.

[0017] The biogas CO2 reforming catalyst (hereinafter simply referred to as CO2 reforming catalyst) 100 of the present invention includes a honeycomb structure made of metal foil 110 and a metal active layer 130 made of metal particles 120 supported thereon.

[0018] As shown in Fig. 1, a honeycomb structure is a structure in which polygonal prism channels (cells) are formed along the central axis direction, and includes not only hexagonal prisms but also a collection of polygonal prism cells such as triangular prisms and quadrangular prisms. The CO2 reforming catalyst 100 of the present invention has such a honeycomb structure, and therefore can facilitate the passage of biogas and promote the reaction. In addition, although Fig. 1 shows a cylindrical honeycomb structure as a whole, the honeycomb structure is not limited to a cylinder and may be a polygonal prism depending on the shape of the reaction tube to be installed.

[0019] The CO2 reforming catalyst 100 of the present invention contains at least nickel (Ni) as the metal particles 120. This enables CO2 reforming of biogas and production of synthesis gas containing hydrogen. Since it is supported on the honeycomb structure 110 with a large surface area, the surface area of ​​the metal active layer 130 can be further increased, and hydrogen can be produced with high efficiency. The CO2 reforming catalyst 100 of the present invention differs from the catalyst of Non-Patent Document 1, for example, in that it does not use alumina.

[0020] So far, there have been reports on steam reforming of methane and CO2 reforming of methane using Ni as a catalyst, but no reports on CO2 reforming of biogas. Surprisingly, the CO2 reforming catalyst 100 of the present invention has excellent carbon deposition resistance, so that catalyst deterioration is small and the reaction tube is not blocked. Such effects will be described in detail in the examples. Each component will be described in detail below.

[0021] The metal foil 110 may preferably be nickel or a nickel-based material mainly composed of nickel, an iron-based alloy mainly composed of iron, or stainless steel. This allows the metal particles 130 to be supported, forming the metal active layer 140. The metal foil 110 is preferably nickel or a nickel-based alloy. This allows the honeycomb structure itself to function as a catalyst, thereby achieving high catalytic activity. In this specification, the amount of the main component means that the content of the metal as the main component is 50 wt% or more.

[0022] The thickness of the metal foil 110 may be, for example, several μm to several hundred μm, and is not particularly limited. From the viewpoint of workability, the thickness is preferably in the range of 20 μm to 100 μm.

[0023] The honeycomb structure preferably has 400 cells / in 2 More than 2500 cells / in 2 The cell density is 400 cells / in 2 By setting the cell density at 2500 cells / in or more, the supporting area of ​​the metal particles 120 can be increased, and the catalytic activity can be improved. 2 By setting the above as described below, it is possible to prevent the pressure loss from increasing when the biogas is passed through the biogas.

[0024] From the viewpoint of catalytic activity, the honeycomb structure preferably has a cell density of 1000 cells / in 2 More than 2500 cells / in 2 Less than 2000 cells / in 2 More than 2500 cells / in 2 It has the following cell densities:

[0025] In the present specification, the cell density is calculated as follows: (length of corrugated foil used in honeycomb structure / pitch distance×2) / cross-sectional area of ​​honeycomb structure.

[0026] The honeycomb structure shown in FIG. 1 is obtained by overlapping a flat metal foil and a corrugated metal foil and rolling them up, but the method for manufacturing the honeycomb structure is not limited to this.

[0027] As described above, the metal active layer 130 is supported on the honeycomb structure and is made of metal particles 120 that are difficult to powder and have excellent thermal conductivity, so that the surface area of ​​the CO2 reforming catalyst 100 can be increased. This enables biogas reforming at a relatively low temperature of about 500 to 800°C, and is far more resistant to carbon deposition than powdered catalysts.

[0028] The metal particles 120 are fine metal particles of 1 μm or less, and preferably have a particle size in the range of 1 nm to 500 nm, which allows stable catalytic activity to be provided.

[0029] More preferably, the metal particles 120 have a particle size in the range of 10 nm to 200 nm, inclusive, which increases the surface area and provides even higher catalytic activity.

[0030] From the viewpoint of catalytic activity and carbon precipitation resistance, the metal particles 120 preferably have a particle size in the range of 50 nm to 195 nm, 50 nm to 180 nm, or 60 nm to 115 nm.

[0031] In the present specification, the particle size is an average value measured for an average of 40 to 100 particles based on an electron microscope image using Image J (ver. 1.51n; open source, public domain image processing software).

[0032] The metal particles 110 preferably contain at least one further metal element selected from the group consisting of rhenium (Re), cerium (Ce), manganese (Mn), molybdenum (Mo), tungsten (W), chromium (Cr), tantalum (Ta), hafnium (Hf), osmium (Os), tin (Sn), zinc (Zn), lanthanum (La), magnesium (Mg), calcium (Ca), scandium (Sc), yttrium (Y), iron (Fe), cobalt (Co), aluminum (Al), silicon (Si), and copper (Cu). This provides even higher catalytic activity and carbon deposition resistance. Among these, the metal particles may further contain Re and / or Ce. These elements can promote biogas reforming at low temperatures, particularly at 500 to 800°C, and can maintain high catalytic activity for a long period of time. More preferably, the metal particles may contain Re and Ce. These elements have excellent resistance to carbon deposition, can further promote the reforming of biogas at low temperatures of 500 to 800°C, and can maintain high catalytic activity for a longer period of time.

[0033] When metal particle 110 contains two or more kinds of metal elements, the metal particle may be an alloy of two or more kinds of metal elements or a mixture of single metals, but from the viewpoint of catalytic activity, an alloy is preferable.

[0034] When the metal particles 110 contain Ni and Re or Ce, Ni is preferably in the range of 10 wt% to 80 wt%, and Re or Ce is in the range of 20 wt% to 90 wt%. Within these ranges, high catalytic activity can be obtained. In this case, Ni is more preferably in the range of 45 wt% to 60 wt%, and Re or Ce is in the range of 40 wt% to 55 wt%. Within these ranges, the metal particles 110 become a stable alloy, and high catalytic activity can be obtained. In this specification, wt% may be expressed as mass percent (mass%).

[0035] Re atoms have a large binding energy with hydrogen atoms, and hydrogen generated on Ni atoms is trapped in the atomic state by the Re atoms. The hydrogen spillover effect suppresses the oxidation of Ni atoms, thereby maintaining high catalytic activity.

[0036] Ce atoms have the ability to store and supply oxygen (oxygen storage ability) by changing their valence from trivalent to tetravalent. When used together with Re, in particular, they suppress atmospheric fluctuations in the vicinity of the Ni-Re alloy catalyst, thereby maintaining high catalytic activity.

[0037] When the metal particles 110 contain Ni, Re, and Ce, Ni is preferably in the range of 10 wt% to 75 wt%, Re is in the range of 5 wt% to 40 wt%, and Ce is in the range of 0.5 wt% to 50 wt%. Within these ranges, high catalytic activity can be obtained. In this case, Ni is more preferably in the range of 25 wt% to 35 wt%, Re is in the range of 25 wt% to 35 wt%, and Ce is in the range of 25 wt% to 35 wt%. Within these ranges, the metal particles 110 become a stable alloy, and high catalytic activity and high carbon precipitation resistance can be obtained.

[0038] The metal active layer 130 may include both metal particles containing only Ni and metal particles containing Ni and an additional metal element.

[0039] Next, an exemplary method for producing the CO2 reforming catalyst of the present invention will be described. FIG. 2 is a flow chart showing the process for producing the CO2 reforming catalyst of the present invention. Step S210: A honeycomb structure made of metal foil is immersed in a solution of a strong acid salt of nickel (Ni) to form a powder layer of a strong acid salt of Ni on the pore surfaces of the honeycomb structure.

[0040] The honeycomb structure may be ultrasonically cleaned in acetone, ethanol, or the like before forming the powder layer of a strong acid salt of Ni.

[0041] The powder layer of a strong Ni acid salt is composed of a strong Ni acid salt or a hydrate thereof, examples of which include Ni nitrates, sulfates, chlorates, bromates, iodates, perbromates, metaperiodates, and thiocyanates. Among these, from the viewpoint of reaction efficiency, Ni nitrates, sulfates, chlorates, and hydrates thereof are preferred.

[0042] The layer of a powder of a strong Ni acid salt may be formed by (A) using an aqueous solution of a strong Ni acid salt of the first element, or (B) treating the pore surfaces of the honeycomb structure with an acid.

[0043] (A) First, a case where a strong Ni acid salt powder layer is formed using an aqueous solution of a strong Ni acid salt will be described. A honeycomb structure is immersed in an aqueous solution of a strong Ni acid salt (e.g., an aqueous solution of nickel (II) nitrate hexahydrate) to form a strong Ni acid salt in the pores and on the surface of the honeycomb structure. Acid salts The amount of the aqueous solution to be coated is preferably in the range of 1 wt % to 20 wt % based on the weight of the honeycomb structure.

[0044] Next, the honeycomb structure coated with the strong Ni acid salt aqueous solution is dried to remove excess solvent, etc., to obtain a honeycomb structure carrying a strong Ni acid salt powder layer made of a strong Ni acid salt or its hydrate. The drying may be left at room temperature for 24 hours, but the solvent can be removed efficiently by drying in two stages. The two-stage drying may be performed at a temperature range of 40°C to 80°C for 3 hours to 10 hours and at a temperature range of 80°C to 150°C for 3 hours to 10 hours. If necessary, the amount of the strong Ni acid salt powder layer may be adjusted by repeating immersion in the strong Ni acid salt aqueous solution and drying.

[0045] (B) Next, a case where a strong acid salt powder layer of Ni is formed by acid treatment using an acid will be described. The acid treatment can be applied when the honeycomb structure is Ni or a Ni-based alloy. Nitrate, sulfuric acid, hydrochloric acid, bromic acid, iodic acid, perbromic acid, metaperiodic acid, permanganic acid, thiocyanic acid, etc. can be used for the acid treatment, and among them, a strong acid selected from the group consisting of nitric acid, sulfuric acid, and hydrochloric acid is preferable from the viewpoint of reaction efficiency. The honeycomb structure is immersed in these strong acids (5% to 20% solution) to react with the strong acid.

[0046] For example, when a honeycomb structure made of Ni or a Ni-based alloy is immersed in nitric acid, the following reaction occurs, and the strength of Ni increases. Acid salt powder As a result, a nickel nitrate layer is formed on the surface and in the pores of the honeycomb structure, and since nickel nitrate is easily soluble in water, it is accompanied by an excess of solvent. Ni+2HNO3→Ni(NO3)2+H2···(1)

[0047] Next, the honeycomb structure coated with the aqueous solution of a strong Ni acid salt is dried to remove excess solvent, etc., to obtain a honeycomb structure carrying a powder layer of a strong Ni acid salt or its hydrate. The drying may be performed in the same manner as described above.

[0048] The treatment (A) may be carried out after the acid treatment (B), which can promote the formation of a powder layer of a strong Ni acid salt.

[0049] Step S220: The strength of Ni obtained in step S210 Acid salts The powder layer is pyrolyzed to form a layer of Ni oxide particles. Acid salts The honeycomb structure carrying the powder layer is then heated and sintered in air. The heating and sintering conditions are as follows: Acid salts There is no particular limitation as long as the powder layer is decomposed, but an example is decomposition in air at a temperature range of 400° C. to 600° C. for a period of 5 hours to 12 hours, thereby obtaining an oxide particle layer made of Ni oxide particles having a particle size range of 1 nm to 500 nm.

[0050] Step S230: The Ni oxide particle layer obtained in step S220 is reduced to form a metal active layer made of metal particles containing Ni. Specifically, the honeycomb structure on which the Ni oxide particle layer is supported may be heated in a reducing atmosphere. The heating conditions are not particularly limited as long as the oxide particle layer is reduced, but for example, the heating conditions are at least 1 hour or more at a temperature range of 400°C to 600°C in a reducing atmosphere of hydrogen, nitrogen, rare gas, etc. The upper limit of the heating time is not particularly set, but since there is no further change even if the heating is performed for 10 hours or more, the upper limit may be 10 hours. Here, the particle size obtained in step S220 is maintained, so that a metal active layer made of metal particles containing Ni having a particle size in the range of 1 nm to 500 nm is obtained. In this way, a carbon dioxide (CO2) reforming catalyst for biogas is obtained, which is provided with a honeycomb structure and a metal active layer made of metal particles containing at least Ni supported on the surface and pores of the honeycomb structure, as described with reference to FIG. 1.

[0051] FIG. 3 is another flow chart showing the process for producing the CO2 reforming catalyst of the present invention.

[0052] Steps S310 and S320 are the same as steps S210 and S220 described with reference to FIG. 2, and therefore a description thereof will be omitted.

[0053] Step S330: In the honeycomb structure having the Ni oxide particle layer obtained in step S320 supported thereon, a powder layer of a strong acid salt of an additional metal element is formed on the Ni oxide particle layer. The additional metal element is at least one selected from the group consisting of rhenium (Re), cerium (Ce), manganese (Mn), molybdenum (Mo), tungsten (W), chromium (Cr), tantalum (Ta), hafnium (Hf), osmium (Os), tin (Sn), zinc (Zn), lanthanum (La), calcium (Ca), scandium (Sc), yttrium (Y), iron (Fe), cobalt (Co), magnesium (Mg), aluminum (Al), silicon (Si), and copper (Cu).

[0054] The powder layer of a strong acid salt of an additional metal element is composed of a strong acid salt of the additional metal element or a hydrate thereof. Examples of the strong acid salt of the additional metal element include nitrates, sulfates, chlorates, bromates, iodates, perbromates, metaperiodates, permanganates, thiocyanates, perrhenates, etc. of the additional metal element. Among these, from the viewpoint of reaction efficiency, nitrates, sulfates, chlorates, and hydrates thereof are preferred.

[0055] The powder layer of the strong acid salt of the further metal element is formed using an aqueous solution of the strong acid salt of the further metal element. Specifically, the honeycomb structure carrying the Ni oxide particle layer is immersed in an aqueous solution of the strong acid salt of the further metal element (for example, an aqueous solution of ammonium perrhenate if the further metal element is Re) to coat the further metal element with the oxide particle layer. The amount of coating is preferably in the range of 0.5 wt% to 10 wt% based on the weight of the honeycomb structure. This allows the further alloying of Ni with the further metal element by the reduction treatment described later, improving the catalytic activity.

[0056] Next, the honeycomb structure having the Ni oxide particle layer coated with the strong acid salt aqueous solution of the further metal element is dried to remove excess solvent and the like, thereby obtaining a honeycomb structure carrying a strong acid salt powder layer made of a strong acid salt of the further metal element or its hydrate. The drying may be left at room temperature for 24 hours, but the solvent can be removed reliably by drying in two stages. The two-stage drying may be performed at a temperature range of 40°C to 80°C for 3 hours to 10 hours and at a temperature range of 80°C to 150°C for 3 hours to 10 hours. If necessary, the amount of the strong acid salt powder layer of the honeycomb structure may be adjusted by repeating immersion in the strong acid salt aqueous solution of the further metal element and drying.

[0057] Step S340: The strength of the further metal element obtained in step S330 Acid salts The powder layer is pyrolyzed to form an oxide particle layer of an additional metal element. This results in a honeycomb structure carrying an oxide particle layer of Ni and an oxide particle layer of an additional metal element. The pyrolysis conditions are the same as those in step S220 of FIG. 2.

[0058] Step S350: The oxide particle layer of Ni and the oxide particle layer of the additional metal element obtained in step S340 are reduced to form a metal active layer made of metal particles containing Ni and the additional metal element. Note that the reduction conditions are the same as those of step S230 in FIG. 2.

[0059] In this way, a catalyst for reforming biogas into carbon dioxide (CO2) is obtained, which includes a honeycomb structure and a metal active layer made of metal particles containing Ni and an additional metal element (the additional metal element is at least one selected from the group consisting of Re, Ce, Mn, Mo, W, Cr, Ta, Hf, Os, Sn, Zn, La, Ca, Sc, Y, Fe, Co, Mg, Al, Si, and Cu) supported on the surface and pores of the honeycomb structure, as described with reference to Fig. 1. When the metal particles are made of two or more elements, some or all of them may be alloyed.

[0060] Alternatively, steps S330 and S340 may be performed first, then steps S310 and S320, and finally step S350.

[0061] FIG. 4 is yet another flow chart showing the process for producing the CO2 reforming catalyst of the present invention.

[0062] Figure 4 is similar to Figure 3, except that step S320 of Figure 3 is omitted and step S340 of Figure 3 is performed simultaneously. Step S410 is the same as steps S210 and S310 described with reference to Figures 2 and 3, and therefore a description thereof will be omitted.

[0063] Step S420: In the honeycomb structure having the Ni strong acid salt powder layer obtained in step S410 supported thereon, a further metal element strong acid salt powder layer is formed on the Ni strong acid salt powder layer. The further metal element is at least one selected from the group consisting of rhenium (Re), cerium (Ce), manganese (Mn), molybdenum (Mo), tungsten (W), chromium (Cr), tantalum (Ta), hafnium (Hf), osmium (Os), tin (Sn), zinc (Zn), lanthanum (La), calcium (Ca), scandium (Sc), yttrium (Y), iron (Fe), cobalt (Co), magnesium (Mg), aluminum (Al), silicon (Si) and copper (Cu). The drying conditions are the same as those in step S330 in FIG. 3, and therefore will not be described.

[0064] Step S430: The Ni ferroelectric powder layer obtained in step S420 and the ferroelectric powder layer of the further metal element are Acid salts The powder layer is pyrolyzed to form an oxide particle layer of Ni and other metal elements. The specific procedure is similar to step S210 in Fig. 2 and step S340 in Fig. 3, so a description thereof is omitted. Unlike Fig. 3, even when preparing a metal active layer made of metal particles containing two or more kinds of metal elements, a single oxidation (pyrolysis) treatment is sufficient, which is efficient.

[0065] Step S440: The oxide particle layer obtained in step S430 is reduced. This forms a metal active layer made of metal particles containing Ni and an additional metal element. Note that the conditions for reduction are the same as those in step S230 in FIG. 2 and step S350 in FIG. 3, and therefore will not be described here.

[0066] In this way, a catalyst for reforming biogas into carbon dioxide (CO2) is obtained, which includes a honeycomb structure and a metal active layer made of metal particles containing Ni and an additional metal element (the additional metal element is at least one selected from the group consisting of Re, Ce, Mn, Mo, W, Cr, Ta, Hf, Os, Sn, Zn, La, Ca, Sc, Y, Fe, Co, Mg, Al, Si, and Cu) supported on the surface and pores of the honeycomb structure, as described with reference to Fig. 1. When the metal particles are made of two or more elements, some or all of them may be alloyed.

[0067] Alternatively, step S420 may be performed first, followed by step S410, and then steps S430 and S440.

[0068] Although the CO2 reforming catalyst 100 has been described as a catalyst for use in carbon dioxide reforming of biogas, the CO2 reforming catalyst 100 of the present invention may also be used as a catalyst for CO2 reforming of methane from natural gas, petroleum, and the like.

[0069] (Embodiment 2) In the second embodiment, a hydrogen production device using the biogas CO2 reforming catalyst of the present invention described in the first embodiment will be described.

[0070] FIG. 5 is a schematic diagram showing the hydrogen production device of the present invention.

[0071] The hydrogen production device 500 of the present invention is typically a fixed-bed flow-type catalytic reaction device. The hydrogen production device 500 includes a supply unit 101 that supplies biogas, and a catalytic reaction unit 102 that includes at least the CO2 reforming catalyst described in the first embodiment and causes a carbon dioxide (CO2) reforming reaction from the biogas, but is not limited to the configuration described below.

[0072] The supply unit 101 supplies at least biogas to the catalytic reaction unit 102. The supply unit 101 may supply an inert gas such as nitrogen or water vapor in addition to the biogas. Supplying water vapor together with the biogas has the effect of suppressing carbon deposition. In this case, for example, the evaporator 103 and the water storage unit 104 may further include a pump 105 and a weighing scale 106.

[0073] The water storage unit 104 stores water that is a raw material for steam. The water storage unit 104 is provided with a weight scale 106, and the amount of water can be measured. This makes it possible to grasp the amount of water supplied to the evaporator 103. Note that the supply unit 101 does not necessarily have to include the weight scale 106.

[0074] The water storage unit 104 is connected to the evaporator 103 via a pump 105. The pump 105 pumps the water sent from the water storage unit 104 to the evaporator 103.

[0075] The evaporator 103 converts water into steam and supplies a mixed gas containing the biogas supplied from a cylinder (not shown) or the like and the steam to the catalytic reaction section 102. The components of the biogas supplied from the cylinder mainly include methane and carbon dioxide.

[0076] The catalytic reaction unit 102 has a reaction tube 107, a CO2 reforming catalyst 10, an electric furnace 109, and quartz wool 108. The CO2 reforming catalyst 10 is the same as the CO2 reforming catalyst 100 described in the first embodiment, so a description thereof will be omitted. The catalytic reaction unit 102 may have a gas chromatograph 510, a cold trap 111, and a flow meter 112. These may be provided as external components of the hydrogen production device 500.

[0077] The reaction tube 107 has a hollow cylindrical shape. As shown in Fig. 5, the reaction tube 107 is arranged with the central axis direction of the cylindrical shape being the up-down direction. The upper part of the reaction tube 107 is connected to the supply unit 101. The reaction tube 107 allows the biogas (containing water vapor as necessary) supplied from the supply unit 101 to flow inside the reaction tube 107.

[0078] The CO2 reforming catalyst 10 is disposed inside the reaction tube 107, and promotes the reaction that produces hydrogen. Quartz wool 108 is disposed above and below the CO2 reforming catalyst 10 disposed inside the reaction tube 107, and fixes the CO2 reforming catalyst 10. The electric furnace 109 has an electric heater and adjusts the reaction temperature to a predetermined value.

[0079] The gas chromatograph 510 is connected to the lower part of the reaction tube 107. The gas chromatograph 510 measures the composition of the exhaust gas discharged from the reaction tube 107. The cold trap 111 is connected to the gas chromatograph 510. The cold trap 111 removes water vapor in the exhaust gas discharged from the reaction tube 107 via the gas chromatograph 510.

[0080] The flow meter 112 is connected to the cold trap 111. The flow meter 112 measures the flow rate of the exhaust gas discharged from the reaction tube 107 via the gas chromatograph 510 and the cold trap 111.

[0081] Next, the operation of the hydrogen production device 500 of the present invention will be described. First, hydrogen is introduced into the catalytic reaction section 102, whereby the CO2 reforming catalyst 10 is subjected to a reduction treatment. This step may be omitted as appropriate. The reaction tube 107 is adjusted to a predetermined reaction temperature by the electric furnace 109.

[0082] Next, biogas (containing water vapor as necessary) is supplied to the reaction tube 107 together with an inert gas such as nitrogen as a carrier gas. For ease of understanding, the biogas will be described as being mainly composed of methane and carbon dioxide. As a result, hydrogen is produced by the carbon dioxide (CO2) reforming reaction shown in formula (2). CH4 + CO2 → 2H2 + 2CO (2) Hydrogen is emitted along with exhaust gases that contain CO (carbon monoxide), residual methane, residual carbon dioxide, etc.

[0083] The hydrogen production device of the present invention does not require a large amount of high-temperature steam, which is expected to save energy. In addition, the use of the CO2 reforming catalyst with excellent thermal conductivity of the present invention enables reforming at a relatively low temperature in the range of 500°C to 800°C, which is expected to further improve energy efficiency.

[0084] Next, the present invention will be described in detail using specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES

[0085] [Honeycomb structure] Pure nickel rolled foil (Ni, foil processing: Nippon Cross Rolling) was corrugated to produce a honeycomb structure with a cell density (number of cells per square inch) of 2300, a diameter of 8 mm, and a height of 10 mm. Table 1 shows the properties of the honeycomb structure.

[0086] [Table 1]

[0087] In Table 1, the structure volume is 0.5024 m 3 The geometric surface area refers to the area of ​​the foil (including the foil for corrugation) required to manufacture one honeycomb structure, and is simply calculated as the length of the foil in a flat state x the width x 2.

[0088] [Preparation of samples for Examples 1 to 4] In Examples 1 to 4, catalysts were produced that had a honeycomb structure provided with a metal active layer made of metal particles containing Ni, metal particles containing Ni and Re, metal particles containing Ni and Ce, and metal particles containing Ni, Re and Ce, respectively.

[0089] First, the sample of Example 1 was prepared. The honeycomb structure was ultrasonically cleaned with acetone, dried, and then impregnated with an aqueous solution of nickel (II) nitrate hexahydrate (concentration 50%) at room temperature to form a powder layer of a strong Ni acid salt (step S210 in FIG. 2). The Ni in the aqueous solution of nickel (II) nitrate hexahydrate was 5% by weight relative to the honeycomb structure. Specifically, the honeycomb structure was impregnated with an aqueous solution of nickel (II) nitrate hexahydrate, dried at 60°C for 6 hours and then at 120°C for 6 hours to remove excess solvent, and a powder layer of a strong Ni acid salt (nickel (II) nitrate hexahydrate) was formed.

[0090] Next, a Ni oxide particle layer was formed from the Ni strong acid salt powder layer (step S220 in FIG. 2). In detail, the honeycomb structure on which the nickel nitrate (II) hexahydrate powder layer was formed was set in an electric box furnace and sintered in air at 500°C for 6 to 8 hours to convert the nickel nitrate (II) hexahydrate into nickel oxide.

[0091] Next, the oxide particle layer was reduced to form a metal active layer of metal particles containing Ni (step S230 in FIG. 2). In detail, the honeycomb structure on which nickel oxide was formed was placed in an electric tubular furnace and reduced in a hydrogen atmosphere at 430° C. for 1 hour to convert nickel oxide into Ni metal. In this way, the sample (Ni5) of Example 1 was prepared.

[0092] The sample of Example 2 was prepared. A honeycomb structure supporting nickel oxide prepared in the same manner as in Example 1 was impregnated with an aqueous solution of ammonium perrhenate (concentration 5%) to form a powder layer of a strong acid salt of Re (step S430 in FIG. 4). The amount of Re in the aqueous solution of ammonium perrhenate was 5% by weight relative to the honeycomb structure. Specifically, the honeycomb structure was impregnated with an aqueous solution of ammonium perrhenate, dried at 60°C for 6 hours and then at 120°C for 6 hours to remove excess solvent, and a powder layer of a strong acid salt of Re (ammonium perrhenate) was formed on the nickel oxide.

[0093] Next, a Re oxide particle layer was formed from the Re strong acid salt powder layer (step S440 in FIG. 4). In detail, the honeycomb structure in which ammonium perrhenate was formed on nickel oxide was set in an electric box furnace and sintered in air at 500°C for 6 to 8 hours to form rhenium oxide on nickel oxide.

[0094] Next, the oxide particle layer was reduced to form a metal active layer of metal particles containing Ni and Re (step S450 in FIG. 4). In detail, the honeycomb structure on which nickel oxide and rhenium oxide were formed was set in an electric tubular furnace and reduced in a hydrogen atmosphere at 430° C. for 1 hour to convert nickel oxide and rhenium oxide into metals of Ni and Re. In this way, the sample (Ni5Re5) of Example 2 was prepared.

[0095] The sample of Example 3 was prepared. A honeycomb structure supporting nickel oxide prepared in the same manner as in Example 1 was impregnated with an aqueous cerium nitrate solution (concentration: 10 wt%) to form a powder layer of a strong acid salt of Ce (step S430 in FIG. 4). The Ce in the aqueous cerium nitrate solution layer was 4.5 wt% relative to the honeycomb structure. Specifically, the honeycomb structure was impregnated with an aqueous cerium nitrate solution, dried at 60°C for 6 hours and then at 120°C for 6 hours to remove excess solvent, and a powder layer of a strong acid salt of Ce (cerium nitrate) was formed on the nickel oxide.

[0096] Next, a Ce oxide particle layer was formed from the Ce strong acid salt powder layer (step S440 in FIG. 4). In detail, the honeycomb structure in which cerium nitrate was formed on nickel oxide was set in an electric box furnace and sintered in air at 500°C for 6 to 8 hours to form cerium oxide on nickel oxide.

[0097] Next, the oxide particle layer was reduced to form a metal active layer of metal particles containing Ni and Ce (step S450 in FIG. 4). In detail, the honeycomb structure on which nickel oxide and cerium oxide were formed was set in an electric tubular furnace and reduced in a hydrogen atmosphere at 430° C. for 1 hour to convert nickel oxide and cerium oxide into metals Ni and Ce. In this way, the sample (Ni5Ce4) of Example 3 was prepared.

[0098] The sample of Example 4 was prepared. A honeycomb structure supporting nickel oxide and rhenium oxide prepared in the same manner as in Example 2 was impregnated with an aqueous cerium nitrate solution (concentration: 10 wt%) to form a powder layer of a strong acid salt of Ce (step S430 in FIG. 4). The Ce in the aqueous cerium nitrate solution layer was 5 wt% relative to the honeycomb structure. Specifically, the honeycomb structure was impregnated with an aqueous cerium nitrate solution, dried at 60°C for 6 hours and then at 120°C for 6 hours to remove excess solvent, and a powder layer of a strong acid salt of Ce (cerium nitrate) was formed on the nickel oxide and rhenium oxide.

[0099] Next, a Ce oxide particle layer was formed from the Ce strong acid salt powder layer (step S440 in FIG. 4). In detail, the honeycomb structure in which cerium nitrate was formed on nickel oxide and rhenium oxide was set in an electric box furnace and sintered in air at 500°C for 6 to 8 hours to form cerium oxide on nickel oxide and rhenium oxide.

[0100] Next, the oxide particle layer was reduced to form a metal active layer of metal particles containing Ni, Re, and Ce (step S450 in FIG. 4). In detail, the honeycomb structure on which nickel oxide, rhenium oxide, and cerium oxide were formed was set in an electric tubular furnace and reduced in a hydrogen atmosphere at 430° C. for 1 hour to convert nickel oxide, rhenium oxide, and cerium oxide into metals of Ni, Re, and Ce. In this way, the sample of Example 4 (Ni5Re5Ce5) was prepared.

[0101] The surface morphology and composition of the samples of Examples 1 to 4 thus obtained were measured using a scanning electron microscope (SEM, manufactured by JEOL, FE-SEM JSM-7000F) equipped with an energy dispersive X-ray analyzer (EDS). The particle sizes of Examples 1 to 4 were calculated from the SEM images for 40 to 100 particles using Image J (ver. 1.51n; an open source, public domain image processing software). The nitrogen adsorption and desorption isotherms of the samples of Examples 1 to 4 were measured using a fully automatic gas adsorption apparatus (manufactured by Microtrack-Bell, BELSORP36), and the BET specific surface area was measured. The results are shown in FIG. 6 and Table 2. [Table 2]

[0102] FIG. 6 shows SEM images of the samples of Examples 3 and 4.

[0103] According to Fig. 6, it was confirmed that a metal active layer made of metal particles was formed on the surface of the honeycomb structure by carrying out the methods of Fig. 2 and Fig. 3. Although not shown, the samples of Example 1 and Example 2 also showed the same morphology.

[0104] Referring to the results in Table 2, the mass percentage of each metal element in the metal active layer was substantially consistent with the charged composition. The particle size of the obtained sample became smaller as the Ni content decreased. In addition, the BET specific surface area of ​​the sample became larger as the Ni content decreased.

[0105] [CO2 reforming of biogas using samples from Examples 1 to 4] The catalytic properties of the samples of Examples 1 to 4 for CO2 reforming of biogas were investigated using a fixed-bed flow-type reactor shown in Figure 5. A simulated gas containing 60% methane and 40% CO2 was used as the biogas. After reduction treatment for 1 hour in a nitrogen stream at 703K (430°C), CO2 reforming was carried out under the conditions shown in Table 3.

[0106] [Table 3]

[0107] The temperature was lowered from 700°C in 50°C intervals and each temperature was held for 5 hours. The gas composition at the outlet was analyzed by a chromatograph 510 (Fig. 5), and the total gas flow rate was measured by a flow meter 112 (Fig. 5). The conversion rate of methane to CO2 was calculated from the above. The internal pressure in the reaction tube 107 (Fig. 5) during the measurement was also measured. The amount of carbon deposition was calculated by thermogravimetric differential thermal analysis (TG-DTA) using a differential thermal and thermogravimetric simultaneous measurement device (Shimadzu Corporation, TG-60) of the sample after the reaction. The weight change was measured while the temperature was raised from room temperature to 1173K (900°C) at a heating rate of 5°C / min and an air flow rate of 50mL / min. The state of the sample after the reaction was also observed by SEM images. These results are shown in Figs. 7 to 10.

[0108] FIG. 7 is a graph showing the methane conversion rate (A) and the CO2 conversion rate (B) by CO2 reforming of biogas using the samples of Examples 1 to 4. FIG. 8 is a graph showing the change in internal pressure in the reaction tube during CO2 reforming of biogas using the sample of Example 4.

[0109] For reference, Fig. 7 and Fig. 8 also show the results of a commercial Ni / Al2O3 granular catalyst (Clariant, FCR-4-02) (simply indicated as FCR-4). Fig. 7 shows that all samples reformed biogas with CO2 in the measured temperature range. In particular, in the measured temperature range, the conversion rate improved in the order of Example 1 (Ni5), Example 2 (Ni5Re5), Example 3 (Ni5Ce4), and Example 4 (Ni5Re5Ce5), and that of Example 4 showed high catalytic activity equivalent to that of the commercial Ni / Al2O3 granular catalyst. This shows that the samples of Examples 1 to 4 function as CO2 reforming catalysts for biogas, and in particular, the sample containing Ni, Re, and Ce showed high catalytic activity, followed by the sample containing Ni and Ce.

[0110] Furthermore, as shown in Figures 7 and 8, Example 4 (Ni5Re5Ce5) showed a high methane conversion rate and the same level of CO2 conversion rate at 700 °C as the commercial Ni / Al2O3 granular catalyst. However, with the commercial Ni / Al2O3 granular catalyst, the methane conversion rate and CO2 conversion rate decreased immediately after the start of the reaction, and the pressure in the reaction tube began to rise 50 minutes after the start of the reaction, and 2 hours after the start of the reaction, the pressure in the reaction tube reached the upper limit set for the reactor (0.2 MPa), and the experiment was forcibly interrupted. This is thought to be due to carbon deposition on the Ni / Al2O3 granular catalyst and the reaction tube being clogged by catalyst powderization. On the other hand, the sample of Example 4 did not show an increase in the internal pressure in the reaction tube. Although not shown, the samples of Examples 1 to 3 also did not show an increase in the internal pressure in the reaction tube. This suggests that the samples of Examples 1 to 4 are biogas CO2 reforming catalysts with excellent carbon deposition resistance.

[0111] FIG. 9 shows an SEM image of the sample of Example 4 after the reaction.

[0112] Comparing Fig. 6(B) before the reaction with Fig. 9 after the reaction, the grain size of the metal particles in the metal active layer was larger. This is believed to be due to the precipitated carbon.

[0113] FIG. 10 shows the TGA curve of the sample of Example 4 after the reaction.

[0114] For reference, FIG. 10 also shows the TGA curve of the commercial Ni / Al2O3 granular catalyst after the reaction. According to FIG. 10, the weight change due to carbon deposition in the sample of Example 4 was 21%, and that of the Ni / Al2O3 granular catalyst was 20%, which was almost the same. However, based on the reaction conditions of the sample of Example 4, which was a reaction time of 1200 minutes (5 hours @ 700 ° C + 5 hours @ 650 ° C + 5 hours @ 600 ° C + 5 hours @ 550 ° C), and the reaction conditions of the Ni / Al2O3 granular catalyst, which was a reaction time of 120 minutes (2 hours @ 520 ° C), it can be seen that the carbon deposition rate in the sample of Example 4 is dramatically slower than that of the commercial Ni / Al2O3 granular catalyst. Although not shown, the samples of Examples 1 to 3 also showed TGA curves similar to those of Example 4. This suggests that the samples of Examples 1 to 4 are biogas CO2 reforming catalysts with excellent carbon deposition resistance.

[0115] From the above, the biogas carbon dioxide (CO2) reforming catalyst of the present invention is equipped with a honeycomb structure made of metal foil and a metal active layer made of metal particles containing at least Ni supported on the honeycomb structure, and therefore exhibits excellent catalytic activity as well as excellent resistance to carbon precipitation and suppression of catalyst powderization.

[0116] [CO2+H2O co-reforming of biogas using samples from Examples 1 to 4] Using the fixed-bed flow-type reactor shown in Figure 5, the catalytic properties of the biogas samples of Examples 1 to 4 for CO2+H2O co-reforming were investigated for the purpose of improving the conversion rate of the biogas and adjusting the composition. A simulated gas containing 60% methane and 40% CO2 was used as the biogas, and water vapor was allowed to flow. After reduction treatment for 1 hour in a nitrogen stream at 703K (430℃), CO2+H2O co-reforming was carried out under the conditions shown in Table 4.

[0117] [Table 4]

[0118] As in the case of CO2 reforming of biogas, the conversion rate of methane to CO2, the internal pressure in the reaction tube, and the amount of carbon deposition were calculated, and the state of the sample after the reaction was observed with an SEM image. These results are shown in Figures 11 to 14.

[0119] FIG. 11 is a graph showing the methane conversion (A) and the CO2 conversion (B) by CO2+H2O co-reforming of biogas using the samples of Examples 1 to 4. FIG. 12 is a graph showing the change in internal pressure in the reaction tube during CO2+H2O co-reforming of biogas using the sample of Example 4.

[0120] For reference, the results of a commercial Ni / Al2O3 granular catalyst are also shown in Figures 11 and 12. Figure 11 shows that all samples co-reformed biogas into CO2+H2O in the measured temperature range.

[0121] In particular, in the measured temperature range, the conversion rate improved in the order of Example 1 (Ni5), Example 2 (Ni5Re5), Example 3 (Ni5Ce4), and Example 4 (Ni5Re5Ce5), and those of Examples 3 and 4 showed high catalytic activity equivalent to that of a commercial Ni / Al2O3 granular catalyst. This indicates that the samples of Examples 1 to 4 function as biogas CO2+H2O co-reforming catalysts, and in particular, the sample containing Ni, Re, and Ce showed high catalytic activity, followed by the sample containing Ni and Ce.

[0122] In addition, by using steam, the methane conversion rates of the samples of Examples 1 to 4 were improved compared to the CO2 reforming of biogas in Figure 7. For example, for the sample of Example 4, the methane conversion rate by CO2 reforming of biogas at 700°C for 5 hours was 55%, but the methane conversion rate by CO2+H2O co-reforming of biogas at 700°C for 5 hours was 75%.

[0123] It should be noted that the wave amplitude in FIG. 11 is larger than that in FIG. 7, but this can be improved by stabilizing the water supply rate.

[0124] Furthermore, as shown in Figures 11 and 12, Example 3 (Ni5Ce4) and Example 4 (Ni5Re5Ce5) showed high methane conversion and CO2 conversion at the same level as the commercial Ni / Al2O3 granular catalyst at 700°C and 650°C. However, with the commercial Ni / Al2O3 granular catalyst, the pressure inside the reaction tube began to rise 20 minutes after the start of the reaction at 650°C, and 3 hours after the start of the reaction, the pressure inside the reaction tube reached the upper limit set for the reactor (0.2 MPa), and the experiment was forced to be interrupted. This is thought to be due to carbon deposition on the Ni / Al2O3 granular catalyst and blockage of the reaction tube due to catalyst powdering.

[0125] On the other hand, the sample of Example 4 did not show an increase in the internal pressure in the reaction tube. Although not shown, the samples of Examples 1 to 3 also did not show an increase in the internal pressure in the reaction tube. This suggests that the samples of Examples 1 to 4 are biogas CO2+H2O co-reforming catalysts with excellent carbon deposition resistance.

[0126] FIG. 13 shows an SEM image of the sample of Example 4 after the reaction.

[0127] Comparing Fig. 6(B) before the reaction with Fig. 13 after the reaction, the grain size of the metal particles in the metal active layer was larger. This is believed to be due to the precipitated carbon.

[0128] FIG. 14 shows the TGA curve of the sample of Example 4 after the reaction.

[0129] For reference, FIG. 14 also shows the TGA curve of the commercial Ni / Al2O3 granular catalyst after the reaction. According to FIG. 14, the weight change due to carbon deposition in the sample of Example 4 was 6%, and that of the Ni / Al2O3 granular catalyst was 11%, so the amount of carbon deposition in the sample of Example 4 was smaller. In addition, based on the reaction conditions of the sample of Example 4 being a reaction time of 1200 minutes (5 hours @ 700 ° C + 5 hours @ 650 ° C + 5 hours @ 600 ° C + 5 hours @ 550 ° C) and the reaction conditions of the Ni / Al2O3 granular catalyst being a reaction time of 400 minutes (5 hours @ 700 ° C + 3 hours @ 650 ° C), it can be seen that the carbon deposition rate in the sample of Example 4 is dramatically slower than that of the commercial Ni / Al2O3 granular catalyst. Although not shown, the samples of Examples 1 to 3 also showed TGA curves similar to those of Example 4. This indicates that the samples of Examples 1 to 4 are catalysts for CO2 reforming of biogas, and that co-reforming with H2O further improves the catalytic activity and carbon deposition resistance.

[0130] From the above, the carbon dioxide (CO2) reforming catalyst of the present invention for biogas has a honeycomb structure made of metal foil and a metal active layer made of metal particles containing at least Ni supported thereon, and therefore exhibits excellent catalytic activity, as well as excellent resistance to carbon deposition and suppression of catalyst powdering. If the CO2 reforming catalyst for biogas of the present invention is co-reformed with H2O, the catalytic activity and carbon deposition resistance can be further improved.

[0131] In addition, in the steam reforming of methane in Patent Document 2, an S / C ratio of 3 or more is required, but in the present invention, as shown in Table 4, the S / C ratio is 1 or less, so there is no need to generate a large amount of high-temperature steam, and a significant energy saving effect is expected (the amount of thermal energy required is 1 / 3 or less of that required in a steam reaction system). [Industrial Applicability]

[0132] The carbon dioxide (CO2) reforming catalyst of the present invention for biogas shows high catalytic activity and has excellent resistance to carbon deposition, and therefore can be used not only for carbon dioxide reforming of biogas but also for carbon dioxide reforming of methane such as natural gas. It is applied to fuel cells for vehicles, fuel cells for mobile phones, fuel cells for portable PCs, stationary fuel cells for home use, hydrogen stations, hydrogen production equipment that supplies hydrogen to semiconductor manufacturing, etc. [Explanation of symbols]

[0133] 100 Biogas carbon dioxide (CO2) reforming catalyst 110 Metal foil 120 Metal particles 130 Metal active layer 500 Hydrogen production equipment 101 Supply section 102 Catalytic reaction section 103 Evaporator 104 Water storage unit 105 Pump 106 Weight scale 107 Reaction tube 108 Quartz wool 109 Electric furnace 111 Cold Trap 112 Flowmeter 510 Gas Chromatograph

Claims

1. A honeycomb structure made of metal foil; a metal active layer made of metal particles supported on the honeycomb structure; Equipped with The metal particles are made of nickel (Ni) and rhenium (Re) or cerium (Ce); The Ni content is in the range of 10 wt % or more and 80 wt % or less, The Re or Ce is in the range of 20 wt % or more and 90 wt % or less. 2 ) Reforming catalyst.

2. The Ni content is in the range of 45 wt % or more and 60 wt % or less, The CO according to claim 1, wherein the Re or Ce is in the range of 40 wt % or more and 55 wt % or less. 2 Reforming catalyst.

3. A honeycomb structure made of a metal foil, a metal active layer made of metal particles supported on the honeycomb structure; Equipped with The metal particles include Ni, Re, and Ce, The Ni content is in the range of 10 wt % or more and 75 wt % or less, The Re is in the range of 5 wt % or more and 40 wt % or less, The catalyst for reforming biogas with carbon dioxide (CO 2 ), wherein the Ce content is in the range of 0.5 wt % to 50 wt %.

4. The Ni content is in the range of 25 wt % or more and 35 wt % or less, The Re is in the range of 25 wt % or more and 35 wt % or less, The CO according to claim 3, wherein the Ce is in the range of 25 wt % to 35 wt %. 2 Reforming catalyst.

5. The CO 2 gas according to any one of claims 1 to 4, wherein the metal particles have a particle size in the range of 1 nm to 500 nm. 2 Reforming catalyst.

6. 6. The CO according to claim 5, wherein the metal particles have a particle size in the range of 10 nm to 200 nm. 2 Reforming catalyst.

7. The CO sintering method according to any one of claims 1 to 6, wherein the metal foil is nickel or a nickel-based alloy, an iron-based alloy, or stainless steel. 2 Reforming catalyst.

8. The honeycomb structure according to any one of claims 1 to 7, wherein the honeycomb structure has a cell density of 400 cells / in2 or more and 2500 cells / in2 or less. 2 Reforming catalyst.

9. A honeycomb structure made of a metal foil is impregnated with a solution of a strong acid salt of nickel (Ni) to form a powder layer of a strong acid salt of Ni on the pore surfaces of the honeycomb structure; forming the Ni oxide particle layer by thermally decomposing the strong acid salt powder layer; The honeycomb structure on which the Ni oxide particle layer is formed is impregnated with a strong acid salt solution of an additional metal element to form a strong acid salt powder layer of the additional metal element on the pore surface of the honeycomb structure; forming a layer of oxide particles of the further metal by pyrolyzing a layer of a strong acid salt powder of the further metal; forming a metal active layer composed of metal particles containing Ni and the further metal element by reducing the oxide particle layer of Ni and the further metal element; Inclusive of The carbon dioxide (CO) of biogas according to any one of claims 1 to 8, wherein the further metal element is rhenium (Re) and / or cerium (Ce). 2 ) A method for producing a reforming catalyst.

10. The method according to claim 9, wherein the pore surfaces of the honeycomb structure are treated with an acid prior to forming the Ni strong acid salt powder layer.

11. The method of claim 10, wherein the acid treatment uses a strong acid selected from the group consisting of nitric acid, hydrochloric acid and sulfuric acid.

12. a supply unit for supplying biogas; Carbon dioxide (CO 2 ) a catalytic reaction section in which a reforming reaction occurs; Equipped with The catalytic reaction section is configured to convert the carbon dioxide (CO) of the biogas according to any one of claims 1 to 8 into 2 2. A hydrogen production device comprising a reforming catalyst.

13. The hydrogen production device according to claim 12 , wherein the supply unit further supplies water vapor in addition to the biogas.

Citation Information

Patent Citations

  • Preparation method for core-shell-structured nickel base methane dry reforming catalyst

    CN104998649A

  • Catalyst for reforming hydrocarbon

    JP2000126595A

  • Water vapor reforming catalyst and producing method thereof

    JP2002028490A

  • Catalyst for producing synthetic gas from natural gas and carbon dioxide and method for producing the same

    JP2011529394A

  • Catalysts and processes for thermal neutralization reforming of liquid hydrocarbons

    JP2016528143A